COMMUNICATION MANAGEMENT OF SEX WORKER TRANSGENDER WITH HIV/AIDS IN FACING SOCIAL STIGMA - Ahmad Fahrul Muchtar Affandi; Tito Edy Priandono; Aly Mecca; Alwan Husni Ramdani (Universitas Djuanda Bogor, 2021)
The common stigma stick to the sex workers is the labeling that they are the cause of the emergence of HIV / AIDS. The stigma is getting compounded for transgender who work as a sex worker. Apart from their work, they are regarded deserving of being infected with HIV because of their 'abnormalities'. Therefore, they face discrimination frequently. The experience of transgender living with HIV is known as overlapping stigma. This study is investigates transgender experience living as sex worker with HIV to confront stigma. Then how is the stigma management of transgender sex workers with HIV. The method used is a case study by conducting in-depth interviews with 8 transgender from West Bandung Regency. The results revealed that stigma experienced by transgender was in the form of physical, social, and moral stigma commit by the external and internal factors. In confronting the stigma, there are two communication strategies adopted by transgender sex workers who are also living with HIV. First, by accepting public perceptions of stigma. The second is challenging public perceptions of stigma. This strategy is manifest in two ways. The first way is to ignore the stigma. The second way is the response this stigma constructive and make it a self-motivation to reach achievements and positive self-concepts.Keywords: communication management, HIV/AIDS, stigma, transgender, sex worker